Back to the vinyl age: a narrative report of a total computer blackout at a large university medical centre. Issue 1 (4th February 2021) - Lehmann, Lorenz H; Meder, Benjamin
Abstract: We report here our experience during a total blackout of all computer systems at a large-scale medical university centre lasting for almost 2 days, affecting not only the hospital information system but also all picture archieving systems, access to laboratory data, office, and email software and even the personnel's ability to log into their accounts. While initially threatening, staff quickly adapted to the situation and the promise of 'digital health' to enable more time for the patient and improve communication, was essentially fulfilled when our computer system was totally down. Based on our experience, we recommend an involvement of health professionals and their medical societies in every step of the digital transformation to accomplish this mission in a responsible, safe, and human-centred way.